2022
DOI: 10.1111/jcms.13362
|View full text |Cite
|
Sign up to set email alerts
|

Moving across Borders: The Work Life Experiences of Czech Cross‐border Workers during the COVID‐19 Pandemic

Abstract: The experiences of cross‐border workers (CBWs) and the difficulties they face during the ongoing COVID‐19 pandemic have been neglected in previous research. CBWs experience various stressors under normal circumstances, where they are often subjected to unequal working conditions and forced to transition between two different societies. The measures that were introduced in response to the COVID‐19 pandemic, including the implementation of physical borders, further worsened the situation for these individuals. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Chilla, 2022). Böhm (2021) confirms the high relevance of the national level for cross-border development in the Polish-Czech border region, as do Haist and Novotný (2022) in the case of the German-Czech border region. Trust, permanent contact points, border-regional risk analyses, harmonization processes, and joint crisis scenarios and exercises as well as strengthened regional competencies can have 'border resilience-promoting' effects.…”
Section: Border-regional Resiliencesupporting
confidence: 58%
See 1 more Smart Citation
“…Chilla, 2022). Böhm (2021) confirms the high relevance of the national level for cross-border development in the Polish-Czech border region, as do Haist and Novotný (2022) in the case of the German-Czech border region. Trust, permanent contact points, border-regional risk analyses, harmonization processes, and joint crisis scenarios and exercises as well as strengthened regional competencies can have 'border resilience-promoting' effects.…”
Section: Border-regional Resiliencesupporting
confidence: 58%
“…Still, the pandemic shows that the national level is necessary for effective crisis cross-border cooperation and border-regional resilience (cf. Böhm, 2021;Chilla, 2022;Haist & Novotný, 2022). Permanent contact points, border-regional risk analyses, harmonization processes, joint crisis scenarios and exercises, and strengthened regional competencies, as well as simple trust, can have 'border-resilience-promoting' effects.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies report on high-income countries, including the USA,24 Canada,25 26 New Zealand,27 Australia,28 Italy,29 and cross-country studies on North America and European countries 30 31. Six studies report on low-income and middle-income countries (LMICs), specifically Thailand,32 Malaysia,33 Ethiopia,16 Poland,34 Czech Republic35 and the African Continental Free Trade Area (ACFTA) countries 36. Ten cross-country studies did not select a specific group of countries based on income 37–46.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies identified in our review focus on the effects of international travel restrictions implemented during early 2020 (n=12) 16 24 26 27 30 32 34–36 41 44 47. The second most studied is the intensity of ITMs in general, using the stringency index of travel measures from the Oxford Coronavirus Government Response Tracker (OxCGRT) 33 39 42 43 45.…”
Section: Resultsmentioning
confidence: 99%
“…The worsening of this barrier complicated the way people living across international borders within CBRs could travel between countries. Early evidence suggests that the erection of partial measures to contrast the diffusion of COVID‐19 within CBRs has caused a significant decrease in the stock of bilateral trust (Haist & Novotný, 2022 ) in all its forms, in particular increasing trade costs, hampering the diffusion of knowledge, and limiting firm cooperation.…”
Section: Measuring the Impacts Of Measures Preventing The Diffusion O...mentioning
confidence: 99%